Does pre-pregnancy BMI determine blood pressure during pregnancy? A prospective cohort study. Issue 8 (11th August 2016) - Savitri, Ary I; Zuithoff, Peter; Browne, Joyce L; Amelia, Dwirani; Baharuddin, Mohammad; Grobbee, Diederick E; Uiterwaal, Cuno S P M
Abstract : Objectives: To evaluate if pre-pregnancy body mass index (BMI) determines blood pressure throughout pregnancy and to explore the role of gestational weight gain in this association. In addition, the effects of pre-pregnancy BMI and gestational weight gain on the occurrence of gestational hypertension and pre-eclampsia were investigated. Design: Prospective cohort study. Setting: Maternal and child health primary care referral centre, Jakarta, Indonesia. Population and measurements: 2252 pregnant women visiting Budi Kemuliaan Hospital and its branch for regular antenatal care visits from July 2012 to April 2015. Pre-pregnancy BMI (kg/m 2 ) was based on self-reported pre-pregnancy weight and measured height at first visit. Gestational weight gain was calculated as weight at the day of delivery minus the pre-pregnancy weight. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured during pregnancy at every visit. Linear mixed models were used to analyse this relation with repeated blood pressure measures as the outcome and pre-pregnancy BMI as the predictor. When looking at gestational hypertension and pre-eclampsia as outcomes, (multiple) logistic regression was used in the analysis. Results: Independent of pre-pregnancy BMI, SBP and DBP increased by 0.99 mm Hg/month and 0.46 mm Hg/month, respectively. Higher pre-pregnancy BMI was associated with higher pregnancy SBP (0.25 mm Hg/kg/m 2 ; 95% CI 0.17 to 0.34; p<0.01) and DBP (0.18 mm Hg/kg/m 2 ; 0.13 to 0.24; p<0.01) in adjusted analysis. Every 1 kg/m 2 higher pre-pregnancy BMI was associated with 6% and 9% higher odds for gestational hypertension (adjusted OR (aOR) 1.06; 95% CI 1.03 to 1.09; p<0.01) and pre-eclampsia (aOR 1.09; 1.04 to 1.14; p<0.01). Accounting for gestational weight gain did not attenuate these associations. Conclusions: Pre-pregnancy BMI determines the level, but not the change, of blood pressure in pregnancy and is linked to higher odds for gestational hypertension and pre-eclampsia, independent of gestational weight gain.